2011
DOI: 10.1245/s10434-011-1669-4
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Effect of Triple-Negative Breast Cancer on Outcome after Breast-Conserving Therapy

Abstract: Patients with TN breast cancer showed significant increases in local and distant metastatic recurrence rates after BCT, and TN status and AA race were independent negative predictors of survival. For the future, identification of these high risk features may bring personalized medicine closer to reality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 18 publications
1
32
0
Order By: Relevance
“…Zaky et al (2011) in their study on outcome of BCT for triple negative tumors showed a high local (12% versus 4%) and distant (15% versus 4%) recurrence rate for TNBC versus Non-TNBC. Triple negative status and African American race were independent predictors of inferior overall survival.…”
Section: Discussionmentioning
confidence: 96%
“…Zaky et al (2011) in their study on outcome of BCT for triple negative tumors showed a high local (12% versus 4%) and distant (15% versus 4%) recurrence rate for TNBC versus Non-TNBC. Triple negative status and African American race were independent predictors of inferior overall survival.…”
Section: Discussionmentioning
confidence: 96%
“…13 TNBC accounts for ∼15%-20% of invasive breast cancers, presents at an advanced histological stage, and is associated with a poor prognosis and a distinct possibility of locoregional recurrence and distant metastasis. [13][14][15][16] Given that TNBC presents with radiotherapy resistance, the development of a radiosensitizer is highly desirable. 17 GNPs have been shown to enhance the sensitization of MDA-MB-231 TNBC cells to 6 MV X-rays with a sensitizer enhancement ratio (SER) of 1.29.…”
Section: Introductionmentioning
confidence: 99%
“…Given the lack of these biologic markers endocrine therapy and HER2-directed therapies are not recommended in the treatment of TNBC [18][19][20].Although the same general principles used in the diagnosis and treatment of non-triple-negative breast cancer generally apply to TNBC, it has a lot of differences in risk factors, molecular and histologic features, clinical behavior and chemotherapy sensitivity [2][3][4][5][6].TNBC defines a heterogeneous mix of breast tumors [7]. TNBC generally has a poorer prognosis among patients with breast cancer [21].…”
Section: Introductionmentioning
confidence: 99%